Design, Modeling, and Characteristics Analysis of Halbach Permanent Magnetic Spring - Yuexuan Lou; He Zhang; Haoran Cai (Actuators)
Magnetic springs, which can be used to replace traditional mechanical springs, have many advantages, such as necessitating no physical contact, generating no friction, no vibration or noise, and having a long lifespan. Nevertheless, their strong nonlinearity limits their widespread application. In this study, we developed a novel permanent magnet spring to address this issue: a Halbach permanent magnetic spring, with a large levitation force and an approximately linear force characteristic curve. First, we introduce the structure and the parameters of the Halbach permanent magnetic spring. Second, we describe the levitation force performance and the stiffness performance of the Halbach permanent magnetic spring using finite element analysis. Third, we analyze the trends through which different parameters influence the levitation force performance and stiffness performance. Finally, we provide recommendations for the future design of and improvement in the Halbach permanent magnetic spring.